Non-Verbal Cognitive Abilities in Children and Adolescents Affected by Migraine and Tension-Type Headache: An Observational Study Using the Leiter-3 - Margari, Lucia; Palumbi, Roberto; Lecce, Paola A.; Craig, Francesco; Simone, Marta; Margari, Mariella; Seccia, Silvana M. C.; Buttiglione, Maura (Frontiers in Neurology, 2018)
Headache is one of the most common neurological disorder in developmental age. Several studies investigated the relationship between headache and emotional/behavioral problems. We studied non-verbal cognitive abilities, including non-verbal memory and attention skills, in order to evaluate the impact of primary headache on these domains. The latest version of the cognitive battery Leiter International Performance Scale – Third Edition (Leiter-3), a non-verbal test, was administered to 35 children and adolescents affected by migraine or tension-type headache and to 23 healthy subjects. We found that frequency of attacks and headache disability (evaluated with the Pediatric Migraine Disability Assessment Score Questionnaire) significantly correlate with nonverbal memory and sustained attention skills. However, we found that headache disability has a significant impact on specific cognitive domains related to sustained attention and nonverbal memory skills. The relationship between headache and memory/attention deficits may have an explanation based on a possible common physiopathology ground, including noradrenergic and dopaminergic pathways.